2021
DOI: 10.1039/d1tc04787f
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of light emitting diodes using photo-patternable quantum dot-acrylate resins

Abstract: We report the preparation of photo-patternable quantum dot (QD)-acrylate resins for application in light-emitting diodes (LEDs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Among these options, acrylic-based resin has been a prevailing choice in the industry for several decades due to features such as its low cost, transparency, and versatility in adjustable functionality. Notably, acrylic resin exhibits excellent chemical compatibility with the hydrophobic nature of QDs, facilitating their effective incorporation with QDs in various applications [27,28].…”
Section: Characterizationmentioning
confidence: 99%
“…Among these options, acrylic-based resin has been a prevailing choice in the industry for several decades due to features such as its low cost, transparency, and versatility in adjustable functionality. Notably, acrylic resin exhibits excellent chemical compatibility with the hydrophobic nature of QDs, facilitating their effective incorporation with QDs in various applications [27,28].…”
Section: Characterizationmentioning
confidence: 99%
“…Simply dispersing QDs with common photolithography or stereolithography resins is therefore not straightforward and can result in aggregation or segregation of the QDs in the organic matrix. 14 As a result, direct photolithography or stereolithography of QDs has often been reported for waterbased systems, 15,16 but such an approach is not compatible with the implementation of oxygen and water vapor barriers. In addition, although depositing thick films of resin by blade coating is relatively easy, maximizing the loading of a QD-resin is highly desirable to minimize the thickness of the colorconverting layer, while maintaining high optical densities.…”
Section: Introductionmentioning
confidence: 99%
“…However, highly emissive QDs are usually synthesized with aliphatic ligands, whereas resins are typically blends of rather polar acrylate-based monomers and crosslinkers. Simply dispersing QDs with common photolithography or stereolithography resins is therefore not straightforward and can result in aggregation or segregation of the QDs in the organic matrix . As a result, direct photolithography or stereolithography of QDs has often been reported for water-based systems, , but such an approach is not compatible with the implementation of oxygen and water vapor barriers.…”
Section: Introductionmentioning
confidence: 99%
“…The CIS/ZnS QDs can also be synthesized via aqueous routes, whereas their PLQYs are much lower . There are many reports regarding fluorescent QD nanocomposites using acrylic resins prepared by UV-curing technique. On the other hand, to the best of our knowledge, celloxide, which is an alicyclic epoxy compound, has not been investigated as a matrix for fluorescent QD nanocomposites yet. The ligand molecule must have (i) a structure similar to that of celloxide and (ii) functional groups, such as thiol or carboxyl, that are easily adsorbed onto the QD surface. , Although our preliminary experiments showed that ligand exchange with cyclohexanethiol improved the dispersibility, the odor was very strong and difficult to handle .…”
Section: Introductionmentioning
confidence: 99%